Detecção molecular de vírus respiratórios em cães - Monteiro, Francielle Liz (2015)
The respiratory viruses of dogs are associated with a disease called canine infectious respiratory disease (CIRD). The main etiological agents of CIRD are canine distemper virus (CDV), canine parainfluenza virus (cPIV), canine adenovirus type 2 and canid herpesvirus type 1 (CaHV-1), which may cause single or mixed infections. CIRD occurs most frequently in places with high animal density and constant movement. CDV, cPIV, CAdV-2 and CaHV-1 infections have been described worldwide, however, few reports of molecular identification of these viruses are available in Brazil. Thus, the objective of this study was to investigate the occurrence of respiratory viruses in dogs in Santa Maria, RS, and in dog shelters in RS, trying to correlate their occurrence with the environmental conditions. Nasal secretions were collected from dogs with respiratory signs submitted to veterinary clinics in Santa Maria; and from dogs of three shelters of RS (Cachoeira do Sul [shelters #1 and #2] and Passo Fundo [shelter #3]). Viral detection/identification was performed by polymerase chain reaction (PCR) for CDV, cPIV, CAdV-2 and CaHV-1. Positive samples were sequenced and, for some viruses, phylogenetic analysis was performed, comparing with sequences deposited in GenBank. Samples of shelters #1 and #3 were obtained during the cold season. Shelter #1 presented poor sanitary and nutrition conditions, high animal density and constant direct contact among dogs. In this shelter 78% (58/74) of the respiratory samples were positive for at least one virus. The single infections were caused by cPIV in 30% (22/74) of the samples and CAdV-2 in 5% (4/74). Coinfections represented 23% (cPIV and CAdV-2); 13% cPIV, CDV and CAdV-2; 4% cPIV-2 and CDV; and 3% CDV and CAdV-2. Shelters #2 and #3 presented satisfactory sanitary and nutrition conditions, with large outdoors exercise areas (#2) and animal separation by groups (#3). In shelter #2, 8% (5/35) of the samples were positive to cPIV and 6% to CaHV-1; in shelter #3, 8% (7/77) of the samples were positive to CAdV-2 and 1% to CDV. Of samples obtained in Santa Maria, 40% (10/25) were positive for virus, being 28% (7/25) for cPIV, and 4% (1/25) to each of the other viruses. Thus, the results obtained demonstrate that infections and coinfections by respiratory viruses are common in shelter dogs in RS, and their occurrence is related to population density, health and nutritional conditions and season. These viruses are also circulating in domestic dogs in Santa Maria, associated with respiratory disease. This study reinforces the importance of preventive measures such as vaccination and good environmental conditions to prevent/reduce infections caused by respiratory viruses in dogs.